THE EUROPEAN UNION (EU) CO-DECIDING AND CO-GOVERNING AUTHORITIES – KNOWLEDGE AND EVALUATION IN THE OPINION OF THE POLES - Greta, Marianna; Tomczak-Woźniak, Ewa; Otto, Jacek (Ekonomia i Prawo. Economics and Law, 2014)
This study concerns the co-decision and co-governing system basing on the European Commission (EC) and the European Parliament (EP) as an example. However, it is not a direct description of functions of these institutions but a presentation of results of empirical studies, including respondents’ knowledge about the EC and EP functioning. In the study the following thesis were verified: awareness and knowledge of the EU institutions is greater in the border regions because of participation in the process of euroregionalisation; level of knowledge about the integration is related to education, the higher and more comprehensive it is, the greater the understanding of the institutionalization of integration; residents of urban areas have greater knowledge about integration than people who live in rural areas.